Strategic Project Management Practices Towards Sustainable Project Performance in Jigawa State Nigeria. - Mubarak Sadis, Aminu; Sadiq, Abba; Sani Usman., Kunya (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Performance of construction projects is retrogressive in most developing economies and could be traced to the poor utilization of project management best practices. The aim of this study is to investigate the strategic project management practices in construction industry of Jigawa state, Nigeria with the view to propose a better strategic project management practice that can be used in Jigawa construction industry. The study adopted random sampling technique using convenient sampling and SPSS software version 22 was used for data analysis and the results were presented in tables. The results indicated that the most project management performance in construction industry in the study area are work with clients who demand quality output, engage high quality managerial staff, excellent track record, provision of adequate equipment to deliver the service and offering superior product and service quality and they were found to be moderate ranked 1st to 5th respectively. Therefore, the study demonstrates the finding where by the model reported R-Value of 0.349 and R-Square value of 0.122 with F-statistics value of 17.178 was significant as showed by ρ-value of 0.000. Therefore, 12.2% of the project management performance is influenced by the strategic project management practices. The study concluded that the least project management performance in construction industry in the study area are training of staff, minimize claims or disputes in the contract and minimize the use of political backing and outside influence in managing project. Construction industry should continue to improve the use of the strategic project management practices that are currently being used. This can be done by providing training to project managers and staff, using project management software, and monitoring and evaluating project performance on a regular basis.